2008
DOI: 10.1111/j.1365-2850.2007.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Should we be ‘pushing meds’? The implications of pharmacogenomics

Abstract: Medication continues to be the most widely prescribed treatment in the NHS for mental health problems. It has been known for many years that individuals differ in the way they respond to a given pharmaceutical therapy, and one reason for this lies in the genetic variation between individuals. This paper recognizes the impact that pharmacogenomics and pharmacogenetics are having in the field of mental health. Variants in genes that code for the drug metabolizing enzymes in the liver have been found to influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It has been found that in the United Kingdom, over 90% of psychiatric patients are prescribed two or more medications at any one time (Commission 2007), which suggests medication is a principal intervention in psychiatric care. It has also been found that certain individuals have severe reactions to medication regimes (Bray et al 2008). There is strong evidence that associates anti-psychotic medication with the development of diabetes and cardiac disease (Reist et al 2007, Smith et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that in the United Kingdom, over 90% of psychiatric patients are prescribed two or more medications at any one time (Commission 2007), which suggests medication is a principal intervention in psychiatric care. It has also been found that certain individuals have severe reactions to medication regimes (Bray et al 2008). There is strong evidence that associates anti-psychotic medication with the development of diabetes and cardiac disease (Reist et al 2007, Smith et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 5–25% of patients receiving neuroleptic medication show no therapeutic benefit (Forman 1993, Usher & Happell 1997) and that patients often continued to receive high doses of neuroleptic medication, despite lack of effect (Usher & Happell 1997). Adherence also does not guarantee freedom from illness or relapse (Bray et al. 2008), with 18–40% of patients diagnosed with psychotic disorders continuing to experience relapses (Kasper 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenetic factors may predict the effects of psychotropic medication in individuals, including discontinuation effects, but genotyping is rare (Bray et al . ). Knowledge to inform best practice (including information exchange with service users about the safest method of withdrawal) has been identified as absent from core MHN education texts (Salomon & Hamilton ).…”
Section: The Effects Of Reducing or Stopping Medicationmentioning
confidence: 97%
“…Among Caucasians, genetically variant metabolizers constitute 20-30 % [10,12]. In spite of this high frequency no large randomized controlled trials have yet investigated the efficacy of pharmacogenetic testing for CYP2D6 [13][14][15][16]. One study has been able to show trends of increased length of hospital stays, higher frequency of ADRs as well as higher costs of treatment amongst psychiatric patients with a genetically deviant metabolizing activity [17] and a recent study found increased risk of switching between antidepressants as well as altered mean maintenance dosages among such patients [18].…”
Section: Introductionmentioning
confidence: 99%